A new freshwater species Achnanthes licunese sp. nov. (Achnanthaceae, Bacillariophyta) from pebbles of Licun River, Shandong Province, China - Chen, Wei; Yu, Pan; Song, Gaofei; Abate, Rediat (Phytotaxa, 2024)
A new freshwater diatom species, Achnanthes licunese sp. nov., was found on pebble samples collected from Licun River in Shandong Province, China. The various taxonomic characteristics of Achnanthes licunese sp. nov. is observed under light and scanning electron microscope. The living cells of A. licunese sp. nov. possesses two chloroplasts. Its valves exhibit a linear to linear-lanceolate outline, slightly constricted in the middle part, with uniseriate striae. The central area of the raphid valves is expanded into a linear and thickened stauros, and the raphe is filiform. On the araphid valves, there is no central area, and the axial area (sternum) is located in the valve margin. The valve of the A. licunese sp. nov. possesses the marginal spines, but no marginal ridge and terminal orbiculi. By comparing the new species with similar Achnanthes species, A. licunese sp. nov. was confirmed to be sufficiently different regarding valve size, striae density, and the presence of marginal spines. The discovery of this species increases the diversity of freshwater diatoms.